Tribute to Duchamp / Ramlan Abdullah - Abdullah, Ramlan (Faculty of Art and Design, 2021)
Ramlan works in a gamut of assorted materials such as metal, stainless steel, copper, and galvanised steel. Copper is somehow sparingly used in Ramlan’s public sculptures, which may hint as a break with the past. His works are often monolithic, as a concatenation of different materials, combining the naturally found or mediated as carved / chiseled/shaped entities. Geometric design in islamic art suggests a remarkable degree of freedom. The complex arrangements and combinations of elements are infinitely expandable. Geometric figure of the circle represents the primordial symbol of unity and the ultimate source of all diversity in creation. The natural division of the circle into regular divisions is the ritual starting point for many traditional Islamic patterns. Aesthetics of Islamicity on the twin stanchions of Beauty and Perfection follow a line of grace, symmetry, harmony, unity, repetition, modulation, peace, proportion, the play of Nur light and refractions. At times, his works play out on another level, acting like a silent ‘doa’ (prayer), in transcending the Tauhid (Oneness with God), and in manifesting the omnipresence of God.